The matriculation story - Abdul Razak, Dzulkifli (Sun Media Corporation Sdn Bhd, 2019)
ENTRY into any educational institution is increasingly getting diverse to reflect the growing diversity of global education. There is always more than one way if diversity in education is to be celebrated, and it is not one size fits all. This is important to improve access and success, especially in addressing heterogeneous situations peculiar to some environment. Since the very term “matriculation” is well accepted in other countries, it tells us that there is nothing wrong with the system per se.